Breaking the Silence: A Phenomenological Study of Student-Initiated Confrontation as Experienced by Social Work Educators - Anderen, Thalia (Canadian Social Work Review / Revue canadienne de service social, 2025)
Mounting evidence suggests that, over the past three decades, post-secondary educators increasingly face concerning behaviours initiated by students, both in and outside of the classroom. The behaviours range from incidental rude and disruptive behaviours to more ongoing, intentional, hostile, aggressive, and even violent behaviours. These student-initiated confrontations (SICs) present personal and professional challenges for educators and are often exacerbated by insufficient institutional support and training with respect to SIC and classroom management. This qualitative phenomenological study aimed to understand the experience of SIC among post-secondary social work educators across Canada and to identify potential strategies to mitigate these challenges. Additionally, the study examined institutional responses to SICs, with a focus on social work education. Particular interest was paid to the implications of SIC for social work education. Fifteen post-secondary social work educators were interviewed using semi-structured interviews, and the data were analyzed using Colaizzi’s descriptive phenomenological approach. Findings suggest that SIC is a present and serious problem within schools of social work that has implications for social work educators, social work education, and the profession itself. Findings specific to social work education suggest that increased mandatory training for educators on classroom management and SIC, as well as increased institutional leadership support for educators, are important in preventing and mitigating this phenomenon.